Plight of the stateless Rohingyas : responses of the state, society & the international community - Ahmed, Imtiaz; Ahmed, Imtiaz, 1958- (Dhaka : University Press, Bangladesh, 2010)
Contributed articles.
Contributed articles.
Includes bibliographical references (pages 211-216) and index.
Keywords: Rohingya (Burmese people) -- Bangladesh -- Government relations; Rohingya (Burmese people) -- Bangladesh -- Social conditions; Refugees -- Government policy -- Bangladesh; Human rights advocacy -- Bangladesh; Human rights advocacy; Refugees -- Government policy; Bangladesh